Chain mediating effect of self-esteem and resilience on the relationship between wellbeing literacy and subjective well-being among college students - Ying Xie; Kai Zeng; Yun Yang; Fangfang Zheng; Feifei Wang (PLoS ONE, 2025)
Based on the framework of psychological capital theory from the perspective of positive psychology, this study explores the influence mechanism of wellbeing literacy on the subjective well-being of college students. In recent years, with the increasing social attention to psychological well-being, wellbeing literacy, as the core element of individuals’ ability to achieve -well-being, has gradually become a focal point in positive psychology research. As a new model for well-being science and practice, wellbeing literacy can provide a tangible way to evaluate mechanisms learned from well-being interventions. This study attempts to investigate both the influence of wellbeing literacy on college students’ subjective well-being and the mediating role of self-esteem and resilience in this relationship. A total of 1030 college students were surveyed using the wellbeing literacy, self-esteem, simplified resilience, life satisfaction, and positive and negative emotion scales. The study results reveal that (1) Wellbeing literacy significantly impacts subjective well-being both overall and directly; (2) Self-esteem significantly mediates the relationship between wellbeing literacy and subjective well-being; (3) A significant chain-mediating effect exists through self-esteem and resilience; (4) The chain-mediating role explains the mechanism underlying this relationship. These findings confirm that wellbeing literacy not only directly promotes subjective well-being, but also cascades through self-esteem enhancement and subsequent resilience improvement. This study provides empirical support for current well-being theory, and recommends stepwise interventions focusing on well-being language cultivation: consolidating the foundation of self-esteem through cognitive reconstruction in early stages, and strengthening stress response training to improve resilience in later phases. Future research can further verify the timing effects of pathways in combination with a tracking design. As a new model for well-being science and practice, wellbeing literacy can provide a tangible way to evaluate mechanisms learned from well-being interventions.